Роль песчанки Виноградова (Mertunes vinogradovi Нерtn.) в полупустынном биогеоценозе - Емельянов, П.Ф.; Найдем, П.Е. (Вестник зоологии, 1976)
The role of the Vinogradov's gerbil is determined in biogeocenosis of the semidesert belt of the Middle-Araksinian trough. Interrelations are considered between the Vinogradov's gerbils, Persian jird, small five-toed jerboa and other rodents. The Vinogradov's gerbil digging activity is stated to have a harmful effect on the soil and plants. The role of gerbils and their fleas in plague epizootic is also shown.